Congenital extrahepatic portosystemic shunt (Abernethy malformation) treated with surgical shunt ligation: A case report and literature review. (2020) - Thirapattaraphan, Chollasak; Treepongkaruna, Suporn; Ruangwattanapaisarn, Nichanan; Sae-Guay, Suthida
Highlights: Abernethy malformation is a rare congenital abnormality characterized by an extrahepatic portosystemic shunt. Doppler ultrasonography is usually the initial investigation. Computerized tomography (CT) scan or magnetic resonance imaging (MRI) scan is helpful in confirming the diagnosis. Preoperative angiography with balloon occlusion test is highly recommended to determine the most appropriate intervention. We propose guidelines for approaching and management this condition. Abstract: Introduction: Congenital extrahepatic portosystemic shunt is also known as Abernethy malformation. It is a rare anomaly of the portal venous system where partial or complete portal blood flow drains directly into the systemic vein via this abnormal shunt, bypassing the liver. Occasionally, this condition is incidentally detected on imaging studies performed for other indications. An early diagnosis is challenging due to the lack of specific symptoms—often leading to delayed diagnosis and development of subsequent complications. Presentation of case: A 4-year-old boy presented with multiple cutaneous hemangiomas with concomitant splenomegaly. While the diagnostic work-up for the definite cause of splenomegaly was in progress, an Abernethy malformation was incidentally noted by abdominal ultrasonography. After computerized tomography (CT) imaging confirmed the diagnosis, the patient underwent a successful surgical shunt ligation without any complications through a one-year follow-up period. Discussion: Various imaging studies, including Doppler ultrasonography, CT imaging, and Magnetic Resonance Imaging (MRI), are useful tools to diagnose an Abernethy malformation. Preoperative angiography with a balloon occlusion of the shunt is highly recommended in order to opt for the most appropriate intervention—including one-or-two-step surgical closure, endovascular occlusion, and liver transplantation. Conclusion: An Abernethy malformation should be considered in the differential diagnosis of unexplained portal hypertension or any of its associated complications in pediatric patients. Early diagnosis and proper management of this condition can lead to a favorable prognosis, as in this case. Accordingly, a pre-operative evaluation is important to determine the proper therapeutic method.